2021
DOI: 10.2147/clep.s312742
|View full text |Cite
|
Sign up to set email alerts
|

Swedish Covid-19 Investigation for Future Insights – A Population Epidemiology Approach Using Register Linkage (SCIFI-PEARL)

Abstract: Background In response to the Covid-19 pandemic, we designed and initiated a nationwide linked multi-register, regularly updated, observational study for timely response to urgent scientific questions. Aim To describe the SCIFI-PEARL (Swedish Covid-19 Investigation for Future Insights – a Population Epidemiology Approach using Register Linkage) linked database encompassing essentially all known diagnosed Swedish Covid-19 patients plus a large general population comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 12 publications
0
46
0
Order By: Relevance
“…The SCIFI-PEARL project is based on a linked and regularly updated database including all registered individuals in Sweden diagnosed with Covid-19, together with a large general population cohort, described in detail elsewhere. 23 The database constitutes a nationwide observational study based on multiple health and population registers linked with high accuracy (close to 100%) and quality using the unique Swedish Personal Identity Number (PIN). 24 The general population comparison cohort was obtained from the National Register of the Total Population (RTB) at Statistics Sweden and comprised about ten percent of all individuals of all ages living in Sweden on 1 January 2020.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SCIFI-PEARL project is based on a linked and regularly updated database including all registered individuals in Sweden diagnosed with Covid-19, together with a large general population cohort, described in detail elsewhere. 23 The database constitutes a nationwide observational study based on multiple health and population registers linked with high accuracy (close to 100%) and quality using the unique Swedish Personal Identity Number (PIN). 24 The general population comparison cohort was obtained from the National Register of the Total Population (RTB) at Statistics Sweden and comprised about ten percent of all individuals of all ages living in Sweden on 1 January 2020.…”
Section: Methodsmentioning
confidence: 99%
“… 19 However, recent research has indicated that taking several overlapping social dimensions into account at the same time can contribute to a more nuanced understanding of socioeconomic disparities in health. 20 , 21 , 22 In the present study, based on data from the nationwide linked multi-register observational study SCIFI-PEARL (Swedish Covid-19 Investigation for Future Insights – A Population Epidemiology Approach Using Register Linkage), 23 we examined sociodemographic determinants associated with Covid-19 vaccination uptake in the general Swedish population aged 60 years or older during the first five months of the Covid-19 vaccination program. Also, heterogeneity within sociodemographic groups was studied by using intersectional analysis models that have previously been suggested for detailed sociodemographic characterisation.…”
Section: Introductionmentioning
confidence: 99%
“…This study is part of the SCIFI-PEARL (Swedish COVID-19 Investigation for Future Insights-a Population Epidemiology Approach using Register Linkage) project, a nationwide multiregister-based observational study designed in response to the COVID-19 pandemic. Details about the project have been published elsewhere 22. Briefly, the project includes regularly updated data of all individuals with COVID-19 identified from different registers in Sweden.…”
mentioning
confidence: 99%
“…The analyses were based on the larger SCIFI-PEARL (Swedish Covid-19 Investigation for Future Insights -a Population Epidemiology Approach using Register Linkage) project, which has been described elsewhere (9). A subproject known as RECOVAC (Register-based large-scale national population study to monitor Covid-19 vaccination effectiveness and safety) focuses on COVID-19 vaccination research questions and this analysis is a first component of that effort.…”
Section: Methodsmentioning
confidence: 99%
“…The study population was identified from national registers at Statistics Sweden, with age and sex data. To this study population we linked data from the National Patient Register (NPR), which includes data on all hospitalizations and outpatient specialist care visits in Sweden, including date of admission or date of visit and diagnoses coded with International Classification of Diseases version 10 (ICD-10) codes, Swedish national version (9).…”
Section: Data Sourcesmentioning
confidence: 99%